Seals and sealing handbook - Flitney, Robert K. (Elsevier Science, 2014)
Seals and Sealing Handbook, 6th Edition provides comprehensive coverage of sealing technology, bringing together information on all aspects of this area to enable you to make the right sealing choice. This includes detailed coverage on the seals applicable to static, rotary and reciprocating applications, the best materials to use in your sealing systems, and the legislature and regulations that may impact your sealing choices. Updated in line with current trends this updated reference provides the theory necessary for you to select the most appropriate seals for the job and.
Keywords: Sealing (Technology) -- Handbooks, manuals, etc.; Sealing (Technology); Seals (Closures); elektronické knihy; electronic books